REVIEW OF THE EVALUATION OF COMMUNITY SERVICE ACTIVITIES BY IMMIGRATION POLYTECHNIC CADETS FOR THE PURPOSE OF VACCINATING IN TANGERANG CITY - Muhammad Mahafada Esa Putra Tugiyono; Rita Kusuma Astuti (Polteknik Imigrasi, 2021)
The purpose of the vaccination program organized by the government is to reduce the possibility of transmission of the Corona virus. If given in bulk, the Covid-19 vaccine can encourage the formation of herd immunity in society. So, people with vulnerable ages such as the elderly and infants or people with autoimmunity and people who can't get vaccinated can still get protection from those around them. Community Service Activities by Immigration Polytechnic Cadets in the context of Vaccination in the Tangerang City area received a positive response in the form of appreciation and thanks delivered directly by the Covid-19 Task Force. It is hoped that this activity is a form of concern and involvement in supporting the government's program to suppress the spread of Covid-19 in Indonesia so that herd immunity can be formed and the pandemic can be ended immediately.